Role of Vitamin D in Prevention of Metabolic Syndrome and Cardiovascular Diseases - Aringazina, Raisa; Kurmanalina, Gulnara; Kurmanalin, Bakhtiyar; Degtyarevskaya, Tatyana (Bangladesh Journal of Medical Science, 2021)
Objective: About 90% of cardiovascular diseases can be prevented. In recent years, the role of vitamin D in the prevention of cardiovascular disease and components of metabolic syndrome has been actively discussed. The study aimed to investigate the possible influence of vitamin D3 on the emergence risk of metabolic syndrome and adverse cardiovascular events. Materials and methods: The study enrolled a total of 336 people (170 males and 166 females) aged 50-60 years. For comparative analysis, two groups were formed: Group 1 group involved 150 people treated with placebo, and Group 2 group included 186 people who received vitamin D3 orally in a dose of 2000 IU/day. The duration of treatment and observation was four years. Participants in the study completed a questionnaire developed by the authors of this paper, in which they answered questions about the presence of factors contributing to the development of cardiovascular pathology. Results and Discussion: Daily oral intake of vitamin D3 in a dose of 2000 IU/day for four years did not improve laboratory indicators, which are components of MS, namely, the content in the blood of TC, TG, LDL, HDL, AI, fasting and postprandial glycemia, insulin, and insulin resistance index HOMA2-IR (p>0.05). Prolonged use of vitamin D3 did not reduce the risk of cardiovascular diseases (myocardial infarcts (RR=0.93, 95% CI [0.21-4.09], p=0.92), strokes (RR=1.24, 95% CI [0.18-8.70], p=0.83), stenting (RR=1,23, 95% CI [0.32-4.88], p=0.76), arterial hypertension (RR=1.12, 95% CI [0.47-2.68], p=0.81), as well as cardiovascular death rates (RR=0.83, 95% CI [0.14-4.88], p=0.83) and death from any other causes (RR=0.93, 95% CI [0.21- 4.09], p=0.92). Conclusion: Thus, daily prolonged oral administration of vitamin D3 in a dose of 2000 IU/day does not contribute to the improvement of blood lipid spectrum, glycemia, and insulin resistance in metabolic syndrome and does not reduce the risk of adverse (fatal and non-fatal) cardiovascular events. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.431-438